Effects of low, medium and high intensity walking on sleep quality and psychological well-being of the elderly women with cognitive impaired - Mosazadeh, Hasan; Rezaei, Zohreh; Dana, Amir (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The rapid growth of aging population, in recent years is the result of a process known as the demographic transition. Cognitive disorders such as dementia and delirium, common problems in older adults, are influenced by deteriorating quality and quantity of sleep and psychological well-being and depression. Aim of Study. The purpose of the present research was to investigate the effectiveness of low, medium and highintensity walking in the quality of sleep and psychological wellbeing of elderly women suffering from cognitive impairment. Material and Methods. A pre-test and post-test quasiexperimental research design was selected for the study. The sample consisted of 80 elderly women in the age range of 60-75 years who were randomized into four experimental groups. Exercise intensity was evaluated and controlled by pedometers. In the pre-test and post-test stages, all subjects completed the Pittsburg Sleep Quality Index and the psychological wellbeing scale. The data analysis was conducted using inferential statistical tests such as repeated measures ANOVA and Bonferroni post-hoc tests. Results. In the pre-test stage (prior to the intervention), the results showed no significant differences between the control and experimental groups in terms of wellbeing, sleep quality and their subcomponents (P > 0.05). In the post-test stage (after the intervention), the results indicated significant differences between control and experimental groups in terms of well-being and sleep quality (P < 0.05). The Bonferroni post-hoc test showed that low, moderate, and high-intensity group had higher scores in sleep quality and well-being compared to the control group (P < 0.05). Conclusions. The results showed that low, moderate, and high-intensity walking has a positive and significant effect on well-being and sleep quality of women with cognitive impairments. Thus, based on these findings, walking is recommended as a useful and health promoting method to improve sleep quality and the well-being of women with cognitive impairments.
Keywords: walking; well-being; elderly women; pedometer; sleep quality